2020
DOI: 10.3390/nu12041106
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Weight Obesity Is Associated with Increased Cardiometabolic Risk in Young Adults

Abstract: Normal-weight obesity (NWO) has been shown to be associated with cardiometabolic dysfunction. However, little is known regarding this potential relationship in early adulthood. The aim of this study was to investigate the associations between NWO and cardiometabolic risk factors in a large population of Colombian young adults. A cross-sectional study was conducted on 1354 subjects (61% women), aged from 18 to 30. Anthropometric data, including body mass index (BMI) and waist circumference (WC), were estimated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 41 publications
4
43
0
5
Order By: Relevance
“…Despite these limitations, the main strength of our study is that, to our knowledge, this is the largest research on the relationship between NWO and cardiometabolic risk in a population of Latin American children and adolescents. These data from adolescents aged 9-17.9 years complement the study published by Correa-Rodríguez et al [25] on the use of the NWO in addition to body adiposity parameters in practice by general practitioners, teachers, and coaches in a school setting. Furthermore, highly standardized procedures were developed within the FUPRECOL study to avoid measurement bias [11].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Despite these limitations, the main strength of our study is that, to our knowledge, this is the largest research on the relationship between NWO and cardiometabolic risk in a population of Latin American children and adolescents. These data from adolescents aged 9-17.9 years complement the study published by Correa-Rodríguez et al [25] on the use of the NWO in addition to body adiposity parameters in practice by general practitioners, teachers, and coaches in a school setting. Furthermore, highly standardized procedures were developed within the FUPRECOL study to avoid measurement bias [11].…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, although the current study focused on the NWO in children and adolescents, this may not necessarily mean that the established health risks of HDL-C and blood pressure can be neglected. Therefore, the present analysis should be reproduced in a larger sample to validate whether in fact the paths are actually similar in both genders [25]. For this reason, given the potential influence of NWO on physical fitness, the findings of our study highlight the importance of considering body composition and CRF levels analysis [26] rather than only measuring BMI in future preventive studies and practices in a school setting.…”
Section: Discussionmentioning
confidence: 70%
“…The expression was introduced by De Lorenzo et al (2006) (7) who adopted it as a criterion for identifying individuals with normal weight, yet with high percentage body fat. Studies carried out in adults indicate positive associations between NWO and cardiometabolic deregulation (8)(9)(10) .…”
mentioning
confidence: 99%
“…BF% is becoming recognized as a more predictive measurement in cardiovascular risk assessment than BMI or waist circumference, and increased BF% was often related to higher CVD risks with the presence of the metabolic abnormalities [ 25 , 68 ]. Genetic studies have suggested that most of the BF% loci also affect cardiometabolic traits and comorbidities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%